2010
DOI: 10.1080/17429145.2010.483744
|View full text |Cite
|
Sign up to set email alerts
|

Changes inEucalyptus camaldulensisessential oil composition as response to drought preconditioning

Abstract: Water deficit, a common constraint in forestry, is the main cause of plant stress during plantation. The survival and growth of seedlings is also compromised by herbivory during establishment. The potential of nursery preconditioning to enhance survival chances of future trees by reducing palatability or attracting beneficial insects as a result of changes in chemical defences may be an answer to overcome this situation. Changes in essential oil production and composition were evaluated by GC and GC-MS in Euca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 23 publications
(27 reference statements)
0
29
0
8
Order By: Relevance
“…Miresmailli et al (2006) and Verma (2012) pointed out the presence of monoterpenes in rosemary whereas Zhang et al (2014) reported its richness in diterpenoid and triterpenoid glycosides. Terpenoids are abundant also in the foliage of E. camaldulensis, providing the characteristic smell as well as being valuable economically and influencing ecological interactions (Leicach, 2010;Külheim et al, 2015). Moreover, in E. camaldulensis oil, monoterpenes were prevalent while sesquiterpene hydrocarbons and oxygenated sesquiterpenes were less represented (Mediouni Ben Jemâa, 2012).…”
Section: Figurementioning
confidence: 99%
“…Miresmailli et al (2006) and Verma (2012) pointed out the presence of monoterpenes in rosemary whereas Zhang et al (2014) reported its richness in diterpenoid and triterpenoid glycosides. Terpenoids are abundant also in the foliage of E. camaldulensis, providing the characteristic smell as well as being valuable economically and influencing ecological interactions (Leicach, 2010;Külheim et al, 2015). Moreover, in E. camaldulensis oil, monoterpenes were prevalent while sesquiterpene hydrocarbons and oxygenated sesquiterpenes were less represented (Mediouni Ben Jemâa, 2012).…”
Section: Figurementioning
confidence: 99%
“…Leaves from seedlings submitted to drought developed an essential oil composition that has been previously reported to be characteristic of mature leaves (Silvestre et al 1997) and related to their higher resistance to herbivory. Total amount of oxygenated terpenes were significantly increased as a result of water deficiency; globulol, epiglobulol, and ledol abundances were doubled, and 1,8-cineole content was enhanced by 28.3%, whereas total amount of non-oxygenated terpenes was significantly decreased (44%) (Leicach et al 2010).…”
Section: Abiotic Factorsmentioning
confidence: 93%
“…Potential of nursery preconditioning to enhance survival chances of future trees by reducing their palatability or by attracting www.intechopen.com beneficial insects as a result of changes in chemical defenses may be an answer to overcome environmental adversities (Leicach et al 2010). It can affect leaves quality by modulating their chemical composition, a determinant feature, besides tissues hardness, towards herbivory.…”
Section: Environmental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh gall wasp-attacked and healthy leaves (100 g each) were cut and immediately subjected to hydrodistillation using Clevengertype apparatus for 3 h (Leicach et al, 2010). The volatile fraction was recovered by decantation and dried over anhydrous sodium sulphate and stored at -20°C until analysis.…”
Section: Isolation Of the Volatile Terpene Fractionmentioning
confidence: 99%